An Analysis of ProjectEdu: A Mobile Learning Application for Software Project Management Education - Fioravanti, Maria Lydia; Oliveira, Raul Donaire Gonçalves; Avellar, Gustavo Martins Nunes; de Oliveira, Camila Dias; Barbosa, Ellen Francine (Learning and Collaboration Technologies. Ubiquitous and Virtual Environments for Learning and Collaboration, 2019)
Learning applications play a key role in educational activities, both in academia and in industry. In this scenario, mobile learning has emerged as a new and promising learning modality, providing more attractiveness, agility, interactivity and flexibility to learners, tutors and teachers in carrying out educational activities and practices. In a different but related perspective, according to ACM/IEEE curricula, Software Project Management is an important topic to be taught in Computing degree programs. Despite its relevance, frequently, there is no specific course to teach Project Management, so its concepts are taught along with the other concepts of Software Engineering. However, even when there is a course dedicated to the subject, in its traditional format, the subject of Project Management is approached in a theoretical way. In this context, it is important to seek strategies that motivate the teaching-learning process, such as, for instance, mobile learning. In order to provide a more interesting approach to learn Software Project Management, we designed, prototyped and evaluated a tool entitled ProjectEdu. In general, users were enthusiastic and positive about the use of the mobile learning application, but they also pointed out some improvement points to make the tool more attractive.